An assessment of the role of the African Union (Au) in combating Al Shabaab terrorism in Somalia; 2006-2016 - Chitsiku, Felistas (Midlands State University, 2016)
The study sought to evaluate the impact of the African Union (AU) in combating Al Shabaab terrorism in Somalia and proffer recommendations on how the AU’s counter-terrorism mission could lead to peace and stability in Somalia. The study was prompted by the escalating incidents of terror attacks and activities which include suicide bombings, killings of civilians, military assaults and destruction of property. This research was accomplished through qualitative methods of data collection and analysis, namely e-mailed questionnaire, textual analysis and in-depth interviews. Findings from this research reveal that the AU has played a fundamental role in bringing the military and political achievements so far in Somalia after a long period of anarchy. Security has greatly improved. AU mission to Somalia, AMISOM, has ousted Al Shabaab from urban centers including the capital city Mogadishu and other small settlements in Somalia. An interim government and some administrative institutions are in place and efforts for restoring peace in the country are underway. Despite the achievements, findings also reveal that Al Shabaab continues to launch attacks on AMISOM bases, for example El Adde recently, on restaurants, beaches etc and has changed tactics to asymmetric attacks using guerrilla tactics. The findings have also indicated AMISOM’s major challenge of inadequate funding to increase equipment and human resources to continue fighting and securing liberated areas as well as blocking Al Shabaab’s supply routes and sources. In light of the setbacks and challenges encountered by the AU’s mission to Somalia, several recommendations have been proffered for the African Union to ensure sustainable peace, security and economic development in Somalia and the whole East African region.